MANAJEMEN KEMITRAAN LEMBAGA PENDIDIKAN DALAM PERSPEKTIF STAKEHOLDER UNTUK MEWUJUDKAN VISI MADRASAH - Suryono Suryono; Rustam Ibrahim (STKIP Pesisir Selatan, 2026)
This study aims to analyze educational partnership management from a stakeholder perspective in realizing the vision of a quality and competitive madrasah. The research employed a qualitative approach using a library research design. Data were collected from various literature sources, including books, scientific journals, research articles, and relevant institutional documents. Documentation techniques were applied in data collection, while data analysis used content analysis through data reduction, data display, and conclusion drawing. The findings reveal that stakeholder-based partnership management plays a strategic role in improving the effectiveness of madrasah governance. Internal stakeholders, including principals, teachers, educational staff, and students, contribute significantly to the implementation of sustainable educational programs. Meanwhile, external stakeholders, such as parents, communities, government institutions, alumni, and institutional partners, support madrasah development through social, moral, and institutional participation. The success of partnership management is influenced by visionary leadership, effective organizational communication, participatory culture, and the strengthening of external collaboration networks. Therefore, stakeholder-based partnership management becomes an essential strategy for enhancing the quality of Islamic education and achieving a collaborative, adaptive, and competitive madrasah vision in contemporary educational contexts.